Before delving deep into the relationship of lines and vectors, there are key differences that you should know when comparing the two:
Line ↔
Vector →
Lines are bi-directional
Vectors are uni-directional
A line is infinite and extends in both direections
Vectors are finite in magnitude
Lines have a definite location
Vectors have no fixed location
Two ines are the equal if they have the same direction and same location
Vectors are the equal if they have the same direction and magnitude
You can describe a line using vectors, and that is what we will explore in some of the equations below.
Vector equation of a line
In a 2D setting (or R), to describe a line in terms of vectors, we need one vector that represents a point on the line and another vector used to describe the direction of the line instead of the slope.
r=r0+tmor(x,y)=(x0,y0)+t(m1,m2)
Where:
t∈R
r=(x,y) is a position vector at any point on the line.
r0=(x0,y0) is a position vector at some point on the line.
m=(m1,m2) is a direction vector parallel to the line.
For a line in R3, the vector equation would be in the form (x,y,z)=(x0,y0,z0)+t(m1,m2,m3)
Here is what the vector equation (x,y)=(−1,1)+t(1,1) looks like compared to the line y=x+2:
The vector r0 represents a point on y=x+2
The vector m represents the slope m=m1m2=11=1
Parametric equations of a line
The parametric equations of a line are equations formed from the individual coordinates of the vectors of the vector equation of a line.
From the vector equation (x,y)=(x0,y0)+t(m1,m2), we get:
x=x0+tm1andy=y0+tm2
If the line is in R3, you also have z=z0+tm3.
Cartesian equation of a line
The cartesian (or scalar) equation of a line is what you already know: y=mx+b, but with a twist!
You must rearrange the equation and multiply it by the common denominators to get an equation of the form:
Ax+By+C=0
A, B and C must be whole numbers, and n=(A,B,C) is the normal vector to the line. The normal vector is a vector that is perpendicular to another.
Here's the graph of the cartesian equation −3x+4y−8=0 looks like compared to its graph y=43x+2:
Again, if the line is in R3, the equation would be in the form Ax+By+Cz+D=0
Example: Vector to cartesian
Convert the vector equation of the line r=(3,−5)+t(−1,−4) to its cartesian form by:
a) Using the vector equation
b) Using the parametric equations
answer
a) We can use the point r0=(3,−5), as well as calculate the slope using m=(−1,−4)
m=m1m2=−1−4=4
Now, substitute these values into the equation of a line:
y−y0=m(x−x0)
y−(−5)=(4)(x−3)
y+5=4x−12
−4x+y+17=0
∴ The cartesian equation of the line is −4x+y+17=0
b) We can use the vector equation r=(3,−5)+t(−1,−4) to form the following parametric equations:
x=3−t
y=−5−4t
Now, rearrange for t:
t=3−x
t=4−5−y
Finally, plug the equations into each other to get the cartesian equation:
4−5−y=3−x
−5−y=12−4x
4x−y−17=0
−4x+y+17=0
∴ The cartesian equation of the line is −4x+y+17=0
Example: cartesian to vector form
Convert the cartesian equation of the plane x+2y−z+6=0 to:
a) Its vector form
b) Its parametric equations
answer
a) To convert to vector form, we need one point, and two direction vectors.
We can get a point by selecting a value for two variables, and solving for the other.
Say x=0 and y=0, then:
x+2y−z+6=0
(0)+2(0)−z+6=0
z=6
So, the point (0,0,6) is on the plane.
To get the two direction vectors, we need to use the plane's normal vector:
n=(1,2,−1)
We can use the dot product to generate vectors that are perpendicular to the normal. These vectors are the direction vectors of the plane.
a(1)+b(2)+c(−1)=0 where (a,b,c) is a direction vector for the plane.
If a=1, b=0 and c=1: (1)(1)+(0)(2)+(1)(−1)=1−1=0⇒ So d1=(1,0,1)
If a=0, b=1 and c=2: (0)(1)+(1)(2)+(2)(−1)=2−2=0⇒ So d2=(0,1,2)
Combining the information we just calculated, we get the vector equation:
π=(0,0,6)+s(1,0,1)+t(0,1,2)
∴ The plane's vector equation is π=(0,0,6)+s(1,0,1)+t(0,1,2)
b) The parametric equations can be derived from the vector equation we just obtained:
x=s
y=t
y=6+s+2t
Symmetric equation of a line in 3D
Note that the vector equation of a line in R3 is (x,y,z)=(x0,y0,z0)+t(m1,m2,m3)
Well, we can rearrange the parametric equations for t:
x=x0+tm1⇒t=m1x−x0,m1=0
y=y0+tm2⇒t=m2y−y0,m2=0
z=z0+tm3⇒t=m3z−z0,m3=0
Now, we just equate them to get the symmetric equation: